2021
DOI: 10.1177/0300060521993691
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous nursing on nursing quality and patient quality of life and satisfaction among children with pneumonia

Abstract: Objective In this study, we aimed to explore the effect of continuous nursing care on children with pneumonia, including patient survival and quality of life. Methods We included 90 children with pneumonia who were admitted to our hospital from May 2017 to June 20, 2017. We established two patient groups (45 children per group); the routine group received general care and the continuous group received continuous nursing care. We observed the correlation among nursing effectiveness, clinical symptom improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In this study, the age and duration of illness had a significant impact on the quality of life. Studies [21,22] on the quality of life reported by children aged 2-18 or 5-18 and their parents have shown that age is one of the factors affecting children's quality of life, and children aged 2 to 5 will affect their normal development because of serious illness, invasive operation and academic interruption. It has been found that there are great changes in diseasespecific and global quality of life for children with recurrent or chronic tonsillitis at 6 months and 1 year after tonsillectomy [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the age and duration of illness had a significant impact on the quality of life. Studies [21,22] on the quality of life reported by children aged 2-18 or 5-18 and their parents have shown that age is one of the factors affecting children's quality of life, and children aged 2 to 5 will affect their normal development because of serious illness, invasive operation and academic interruption. It has been found that there are great changes in diseasespecific and global quality of life for children with recurrent or chronic tonsillitis at 6 months and 1 year after tonsillectomy [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…This not only reduces unnecessary waste of medical resources but also increases patients and their families sense of security. [ 27 ] However, due to severe shortages of human and material resources, many traditional continuous care models, such as telephone follow-up, network information platform follow-up, specialist nurse follow-up, home visits, family video conferences, health knowledge lectures, and community activities, are considered too formal and rigid and not flexible enough to meet the requirements of outpatient care. The continuous care team model is characterized by being led by a head nurse, with doctors and nurses participating, and management coordination and regular follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical education integration component (TPS triangle) is one of the components of this model (Vosoughi et al, 2022 ). The nursing process was used as a strategy during this component to: 1.use a common language between education and clinical setting (attending nurse teachers, nursing students and nurses; Gonçalves & Sequeira, 2019 ; Mousavinasab et al, 2020 ), 2. provide a factor that creates continuous care among caregivers (Liu et al, 2021 ) and 3. achieve evidence‐based education and practice (Oreofe & Oyenike, 2018 ). The aim of this study was to investigate the effectiveness of institutionalizing the nursing process in the form of the TPSN model on the quantity and quality of nursing diagnoses.…”
Section: Introductionmentioning
confidence: 99%